(3QSGdI aj GdehSjbis
(3ChdgG (B:s
(3GdefGSHGJ GdeTghQg ai gPG GdYGde YTQI , KdGKI efgG CTgQ , hgj GdefGSHGJ GdYOhjI , hGdeHGjfI GdgfOSjI hGdeHGjfI GdJCdjajI s
(3BNQgG (B:s
(3dChQOJ WQakG ef WQa eHGMKJgG hdHGHkG ef YHGH eaGMUgG agPG BNQ eG CQOJ EjQGOg ai gPG GdMd s
(3jfbd Yf GdQSGdI GdTQbjI ddCQeis
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B4 - (3bSe eYGQa YGeg (B- (3U (B57 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
Keywords: (3GdehSjbi hGdZfGAs